2015
DOI: 10.1378/chest.14-1992
|View full text |Cite
|
Sign up to set email alerts
|

Chemoreceptor Responsiveness at Sea Level Does Not Predict the Pulmonary Pressure Response to High Altitude

Abstract: Abstract:The hypoxic ventilatory response (HVR) at sea level (SL) is moderately predictive of the change in pulmonary artery systolic pressure (PASP) to acute normobaric hypoxia. However, because of progressive changes in the chemoreflex control of breathing and acid-base balance at high altitude (HA), HVR at SL may not predict PASP at HA. We hypothesized that resting peripheral oxyhemoglobin saturation (SpO 2 ) at HA would correlate better than HVR at SL to PASP at HA. In 20 participants at SL, we measured no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Based on our previous exercise and high-altitude studies (e.g. [ 16 21 ]) adequate sample sizes for each of the outlined studies, accounting for potential subject dropout, were determined by related statistical power calculations whereby a power of 0.8 was assumed, and an alpha value of 0.05 was set (G*power). Depending on the variability of the primary outcome of each study (e.g., CBF, PASP, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous exercise and high-altitude studies (e.g. [ 16 21 ]) adequate sample sizes for each of the outlined studies, accounting for potential subject dropout, were determined by related statistical power calculations whereby a power of 0.8 was assumed, and an alpha value of 0.05 was set (G*power). Depending on the variability of the primary outcome of each study (e.g., CBF, PASP, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Although the steady-state hypoxia test aims to target the peripheral chemoreceptors, quantification of the ventilatory responses may be confounded by the duration of these tests (e.g. 10-20 min; Steinback & Poulin, 2007;Hoiland et al 2015b). For example, variable changes in P aCO 2 during the steady-state poikilocapnic hypoxia test can dramatically modify the ventilatory response magnitude (Steinback & Poulin, 2007).…”
Section: Advantages and Utility Of The Transient Testsmentioning
confidence: 99%
“…A feature of our comparison of the ventilatory and the pulmonary vascular acclimatization to hypoxia is the finding that the two physiological processes show no correlation. Perhaps in keeping with this a recent study at high altitude found no correlation between the eucapnic hypoxic ventilatory response measured at sea level and the elevation in PASP measured at an altitude of 5050 m (Hoiland et al 2014). .…”
Section: Differences Between the Ventilatory And Pulmonary Vascular Amentioning
confidence: 55%
“…Perhaps in keeping with this a recent study at high altitude found no correlation between the eucapnic hypoxic ventilatory response measured at sea level and the elevation in PASP measured at an altitude of 5050 m (Hoiland et al . ).…”
Section: Differences Between the Ventilatory And Pulmonary Vascular Amentioning
confidence: 97%